Rabies serology: relationship between assay type, interpretation, and application of results - Moore, Susan M. (Kansas State University, 2015)
The immune status of an individual host or among a population is affected by important variables including the source and route of potential natural exposure and for vaccination consist of vaccine type, potency, and virus strain; vaccination route and schedule; and individual host factors. Although, perhaps, often overlooked, it is essential to have a basic understanding of the laboratory methods used to measure and assess the host’s immune status. The precision, accuracy, sensitivity, and specificity of a method must be well defined. Moreover, an “adequate,” acceptable, or diagnostic value for each method must be clearly defined so that a particular test result for a patient can be meaningfully interpreted in relation to the patient’s history and clinical management. The reasons for performing rabies serology can range from diagnosis of infection to investigation of epitope specificity of an anti-rabies virus glycoprotein monoclonal antibody. Characterization of an antibody’s affinity, specificity, quantity, and neutralizing function, and class/subclass are achieved by various methods. Many serological techniques developed over the past five decades differ not only in their ability to detect the function, affinity and specificity of rabies virus antibodies, but also in the ease and practicality with which they are performed. To select an appropriate method and appropriately interpret test results, it is essential to understand the specific strengths, weaknesses, and limitations of available methods. The decision to use a specific assay should start with the purpose of testing and the intended application of results. Other factors to consider are the assay complexity, degree of precision and/or accuracy, specificity and range of detection. Given the importance of RVNA levels in the prevention of human and animal rabies, guidelines for adequate vaccination should be stated in terms that are readily understood by individuals-at-risk and health care providers, both veterinary and medical, who will use the recommendations for clinical management of humans or animals. Across the globe, the standardization of rabies serologic assays has a direct effect on the clinical use of human and animal products, including direct assessment of, and assessment of host responses to, rabies vaccines for the prevention of rabies.
Keywords: Immunology; Rabies; Serology; Vaccinology; Public Health (0573)